2016
DOI: 10.1007/s00726-016-2342-9
|View full text |Cite|
|
Sign up to set email alerts
|

Glutamate and α-ketoglutarate: key players in glioma metabolism

Abstract: Glioblastoma multiforme (GBM), or grade IV astrocytoma, is the most common type of primary brain tumor. It has a devastating prognosis with a 2-year-overall survival rate of only 26 % after standard treatment, which includes surgery, radiation, and adjuvant chemotherapy with temozolomide. Also lower grade gliomas are difficult to treat, because they diffusely spread into the brain, where extensive removal of tissue is critical. Better understanding of the cancer’s biology is a key for the development of more e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 82 publications
(89 reference statements)
1
62
0
3
Order By: Relevance
“…The data showed that the levels of glutathione (GSH), glutamate (Glu), and alpha-ketoglutarate (aKG) were most significantly increased in MFN1-overexpressed primary mouse mammary epithelial cells as compared with the control cells (Table S1; n = 3, >2.5fold, p < 0.05). Mitochondrial fusion is linked to enhanced TCA cycle activity (Mishra and Chan, 2016), and aKG, a TCA intermediate metabolite, can be converted to synthesize Glu, which further leads to the synthesis of GSH, an antioxidant that plays a pivotal role in scavenging and reducing mitochondrial and intracellular ROS (Harris et al, 2015;Maus and Peters, 2017;Figure S4E). We found that, similar to ectopic expression of MFN1, TGFb1 treatment led to increased GSH, Glu, and aKG levels, which were reversed upon knockdown of MFN1 in MCF12A cells ( Figures S4F-S4H).…”
Section: Resultsmentioning
confidence: 99%
“…The data showed that the levels of glutathione (GSH), glutamate (Glu), and alpha-ketoglutarate (aKG) were most significantly increased in MFN1-overexpressed primary mouse mammary epithelial cells as compared with the control cells (Table S1; n = 3, >2.5fold, p < 0.05). Mitochondrial fusion is linked to enhanced TCA cycle activity (Mishra and Chan, 2016), and aKG, a TCA intermediate metabolite, can be converted to synthesize Glu, which further leads to the synthesis of GSH, an antioxidant that plays a pivotal role in scavenging and reducing mitochondrial and intracellular ROS (Harris et al, 2015;Maus and Peters, 2017;Figure S4E). We found that, similar to ectopic expression of MFN1, TGFb1 treatment led to increased GSH, Glu, and aKG levels, which were reversed upon knockdown of MFN1 in MCF12A cells ( Figures S4F-S4H).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the limited availability of AKG in aged mice, under cold stimulus, DNA demethylation in the Prdm16 promoter was hampered in aged mice. Because AKG is absorbable by cells (Maus & Peters, ), we supplemented middle‐aged mice with AKG and found that dietary supplementation of AKG could elevate their circulatory level and the availability of AKG for beige adipogenesis. We found AKG was elevated in BAT and iWAT after cold exposure, which acted as a cofactor facilitating the DNA demethylation of brown adipogenesis genes.…”
Section: Discussionmentioning
confidence: 99%
“…During aging, however, the cellular metabolic flux declines, which is expected to reduce the AKG concentration in nuclei and thus impede DNA demethylation and brown adipogenesis. As a small molecule, extracellular AKG can be actively absorbed and transported into cells (Burckhardt et al, ; Maus & Peters, ). Thus, we hypothesized that dietary supplementation of AKG could elevate its level in the circulation and, thus, the availability of AKG for beige adipogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The mutated enzyme catalyzes NADP+/NAD+-dependent conversion of isocitrate to 2-hydroxyglutarate (2HG), while the wild type converts isocitrate to α-ketoglutarate. As a consequence this metabolite accumulates in the cell and is further able to affect the demethylating process in the genome (Maus and Peters 2017). Thus 2HG is also known to be an “oncometabolite”.…”
Section: Discussionmentioning
confidence: 99%